Social networks as technology education (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
The technologies of learning and communication have come to revolutionize the different forms of education, a virtual teaching to which school institutions are linked with feasible spaces to bring the teaching to each person according to their learning style. Social networks have become an educational technology, a learning tool that is used more and more day in the educational environment based on communication and collaborative work. Therefore the present research analyzes the social networks as educational technologies, realized in the University Center of the North, University of Guadalajara Mexico, from where the simple random sample was taken participating in the method of survey and data analysis of the program SPSS, SPSS (Statistical Package for the Social Sciences). Starting from the fundamental axes of social networks research is carried out to make known the results of the usefulness of the new technology in education. The results show that social networks are the new technologies for education.
Keywords: Social networks; education; learning; technologies